The Effect of Organizational Culture, Motivation, and Self-Leadership on Student Performance In Start-Ups - Amalia Putri Ghassani; Wirawan ED Radianto; Stanislaus Mastan (Indonesian Journal of Business and Entrepreneurship (IJBE), 2020)
The development of entrepreneurial education designed currently is developing rapidly. One of the goals of this education is to produce new start-ups. Therefore, factors that impact the performance of start-ups by university students are important to be studied further. This study aimed to determine the impact of organizational culture, motivation, and self-leadership on the performance of students of the Accountancy Study Program in a private university in Surabaya, which has entrepreneurship as part of their curriculum. This private university is a university with the vision of creating entrepreneurs. Therefore, the learning method provided is project-based learning. All students have to undergo entrepreneurship learning, and thus, they are required to create start-ups according to their field of study and according to their respective study program. The success of the students' start-ups will undoubtedly require excellent performance in achieving the set target. This study was conducted using a quantitative method and analyzed using multiple regression analysis. The result of this study suggested that organizational culture and self-leadership had an impact on students' performance in start-ups. However, motivation had no impact on students' performance in start-ups. Keywords: entrepreneurial education, organizational culture, performance, motivation, self-leadership